The Effect of Imagery Training in Increasing the Confidence - Putri Cicilia Kristina; Endie Riyoko; Perabunita Perabunita; Daryono Daryono (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the effect of mental imagery training on increasing Athletes' Confidence in facing the competition at the Futsal Athletes of the Musi Banyuasin Club, South Sumatra. This type of research is an experiment with the design of "The One Group Pretest-Postest Design". The population in this study were athletes at the Musi Banyuasin Futsal Club, South Sumatra, totaling 24 athletes. The sampling technique used total sampling. Data analysis using t-test with significance level. The method in this study is an experimental design with a pretest-posttest design group. The data were analyzed using t-test statistics. The results showed that the average self-confidence pretest was 71.67, and posttest was 92.50. While the results of hypothesis testing with a 95% confidence level or an error rate 5%, indicated by the coefficient value tcount > ttable or 10,618 > 1,714, then reject Ho and accept Ha, meaning the hypothesis which reads There is an effect of Imagery Exercise on increasing Athletes' Confidence Futsal in facing the match accepted the truth.